Nanoberries for topical delivery of antioxidants - Martinetti Montanari, Jorge Anibal (2013)
With the aim of improving the antioxidant activity of polyphenols from blueberries (Vaccinium myrtillus) on skin targets after topical application, ethanolic extracts from three blueberry varieties (named Millenia, O?Neal and Blue Crisp) were loaded into ultradeformable liposomes. These nanocarriers are known to be capable of penetrating through the stratum corneum reaching its deeper layers and the viable epidermis. On the other hand, blueberries contain large amounts of polyphenols, whose antioxidant properties as tissue protectors against processes mediated by reactive oxygen species have been extensively proved. Blueberries are usually consumed as edible products, but their antioxidant compounds are poorly absorbed. The antioxidant properties of the extracts were screened before and after being loaded into ultradeformable liposomes made of soy phosphatidylcholine and sodium cholate, of nearly 100 nm in size at 0.223 extract/lipid w/w. The ethanolic extract-loaded ultradeformable liposomes (nano-berries) from Millenia variety retained an 85 % of the antioxidant capacity of the free extract and showed low cytotoxicity on HaCaT cells (less than 20%) at active concentration against free radicals.